A Train to Castle Von Aux: Patrick deWitt’s Fiction and the Transnational Paradigm - Majer , Krzysztof (Hungarian Journal of English and American Studies, 2020)
While deWitt’s writing enjoys commercial and critical success, it has inspired very little academic scrutiny. This is perhaps due to deWitt’s avoidance of Canadian settings and themes in favor of motifs from American popular culture or European folktales. Just as The Sisters Brothers (2011) relied on deWitt’s ironic use of the Western formula, so Undermajordomo Minor (2015) constitutes a playful attempt at rejuvenating several tired genres. In the story of young Lucy Minor’s acquisition of a dubious post at the eerie Castle Von Aux there are unmistakable elements of the Gothic romance, the fable, and the Bildungsroman, all spiced up with a quirky cinematic aesthetic. Equally strong are the echoes of Walser’s Jakob von Gunten, Kafka’s The Castle, and Bernhard’s Gargoyles, themselves richly interconnected. Through these diverse allusions and a curious blurring of geographical and historical boundaries, deWitt creates transgeneric fiction, which may be understood as transnational in the sense assumed by Kit Dobson or Peter Morgan.